Settlement of Gracilaria gracilis carpospores (Gracilariales, Rhodophyta) on natural substrates from the southwestern Atlantic coast (Chubut, Argentina) - Hughes, Melanie Hebe (2014)
Gracilaria gracilis is an important agarophyte that is exploited in Argentina by the harvest of detached thalli cast on the shore. Therefore, the study of carpospores is relevant because such spores can be used as inoculum for commercial aquaculture. In this study, the potential of two natural substrates from the Patagonian coast, for the settlement and growth of G. gracilis carpospores, was evaluated in the laboratory. Highly significant differences were found between substrates both in the proportion of substrates with settled spores and in carpospore density, shells being more suitable than pebbles. Regarding carposporeling growth, differences in sporeling length between substrates could not be detected by the end of the study, although basal discs reached a significantly higher diameter on pebbles than on shells. Results indicate that shells would be a good substrate to start spore culture because they offer a suitable surface for spore settlement. In addition, if the substrate is inoculated with sufficient seedling material to avoid competition among individuals and, if epiphytism is successfully reduced, sporelings should reach the required size for transport to the natural environment.